A new species of Cyrtodactylus Gray, 1827 (Squamata: Gekkonidae) from the Thai-Malay Peninsula and the independent evolution of cave ecomorphology on opposite sides of the Gulf of Thailand - Grismer, L. Lee; Pawangkhanant, Parinya; Idiiatullina, Sabira S.; Trofimets, Alexei V.; Nazarov, Roman A.; Suwannapoom, Chatmongkon; Poyarkov, Nikolay A. (Zootaxa, 2023)
An integrative taxonomic analysis recovers a distinctive new species of the gekkonid genus Cyrtodactylus Gray, 1827 from Satun Province in extreme southern Thailand as the sister species to the Cyrtodactylus intermedius group of southern Indochina, approximately 600 km to the northeast across the Gulf of Thailand. Based on 1449 base pairs of the mitochondrial gene NADH dehydrogenase subunit 2 (ND2) and its flanking tRNAs, the new species, C. disjunctus sp. nov., bears a pairwise sequence divergence from the mean divergences of the intermedius group species ranging from 17.9–23.6%. Three different principal component analyses (PCA) and a multiple factor analysis (MFA) recover C. disjunctus sp. nov. as a highly distinctive karst cave-adapted species based on morphology and color pattern. Its sister species relationship to the intermedius group—to which it is added here—further underscores a growing body of analyses that have recovered a trans-Gulf of Thailand connection across the submerged Sunda Shelf between the southern Thai-Malay Peninsula and southern Indochina. Fragmented karstic archipelagos stretching across Indochina have served as foci for the independent evolution of nearly 25% of the species of Cyrtodactylus. The description of C. disjunctus sp. nov. continues to highlight the fact that karstic habitats support an ever-increasing number of threatened site-specific endemics that compose much of the reptile diversity of many Asian nations but, as of yet, most of these landscapes have no legal protection.